Pengaruh Model Cooperative Integrated And Composition (CIRC) Terhadap Kemampuan Menulis Teks Eksplanasi Pada Siswa Kelas VIII SMP Swasta Islamiyah Hessa Air Genting Tahun Ajaran 2023/2024 - Nuraini Nuraini; Muhammad Surip (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aims of this research were to (1) determine the ability to write explanatory text in class VIII of Hessa Air Genting Private Middle School Islamiyah before using the Cooperative Integrated Reading and Composition (CIRC) Model, (2) determine the ability to write explanatory text in class VIII of Private Islamiyah Middle School Hessa Air Genting after using the Cooperative Integrated Reading and Composition (CIRC) Model, and (3) knowing the influence of the Cooperative Integrated Reading and Composition (CIRC) Model on the ability to write explanatory texts in Class VIII Students of Hessa Air Genting Private Islamic Middle School. This research involved all 114 class VIII students, with a sample of 78 people who were divided into two classes: control class (39 people) and experimental class (39 people). The instruments used include general statements, series of events, closings, causal conjunctions, chronological conjunctions, pronouns, and technical words. The experimental method used is a two group post-test with a quantitative approach, and uses data analysis techniques such as analysis requirements tests, normality tests, and hypothesis tests. The results of the research show that the ability to write explanatory text using the Cooperative Integrated Reading and Composition (CIRC) Model has a significant impact, as evidenced by the value of tcount > ttable (5.64 > 2.02439), indicating a significant increase in the ability to write explanatory text for class VIII students at Hessa Air Genting Private Islamic Middle School in the 2023/2024 academic year.